Research methods in environmental law : a handbook - Philippopoulos-Mihalopoulos, Andreas; Brooks, Victoria; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
This timely Handbook brings together a collection of innovative interdisciplinary approaches to explore the use of research methods in environmental law. With chapters on topics ranging from sustainability, climate change and activism to education, actor-network theory and non-human ontologies, this Handbook provides a theoretically informed analysis of methodological approaches to this important field. Taking into consideration issues such as non-human agency, the Anthropocene, and spatial and material turns in law this book builds on key concepts in the subject. The book also considers how environmental law must adapt to the new and urgent needs of a variety of bodies, both human and non-human, that require its protection. It argues that traditional ways of conceiving environmental law, and of accounting for problems brought about through anthropocentric means, have led to the reinstatement of the problem of environmental degradation without imagining different avenues to resolve it. This Handbook is a key addition to the existing literature and provides an invaluable contribution to practical critique and to the reimagining of environmental law. It will be a crucial compendium for graduate students and researchers in the field of environmental law wishing to explore critical approaches.
Part I: Materiality -- 1. Foregrounding vulnerability: materiality's porous affectability as a methodological platform / Anna Grear -- 2. How to think about 'nature-society' interactions in environmental law 'in action'? / Betina Lange -- 3. Abstracting method: taking legal abstractions seriously / Andrea Pavoni -- 4. Actor-network theory and the empirical critique of environmental law: unpacking the bioprospecting debates / Emilie Cloatre -- 5. Speculative entropy: dynamism, hyperchaos and the fourth dimension in environmental law practice / Lucy Finchett-Maddock -- 6. Critical environmental law as method in the anthropocene / Andreas Philippopoulos-Mihalopoulos -- Part II: spatiality and jurisdiction -- 7. Place-thinking: the hidden geography of environmental law / Robyn Bartel -- 8. Bringing environmental justice to the centre of environmental law research: developing collective case study methodology / Jane Holder and Donald McGillivray ---9. Third Word Approaches to International Law (TWAIL) and the environment / Usha Natarajan -- 10. The methodology of environmental constitutional comparison / Francois Venter and Louis Kotze -- 11. Engaged enquiry in environmental law: understanding people/place connections through a geographically informed human rights lens / Jo Gillespie -- Part III: Ecology, economics and political activism -- 12. ecofeminist approaches to the construction of knowledge and coalition building - offering a way forward for international environmental law and policy / Karren Morrow -- 13. Environmentalism and an anarchist research method / Peter Burdon and James Martel -- 14. On the relation between scholarship and action in environmental law: method, theory, change / Andreas Kotsakis -- 15. A systems theory perspective on the principle of precaution employing critical discourse analysis / John Paterson ---16. Environmental law in the age of the anthropocene: how to normatively communicate on environmental change and risks? / Inger Johanne Sand -- 17. The nested eye: naturalism, perspectivalism, and environmental law / Ben Woodard -- Part IV: More-than-human -- 18. thinking about law and the question of the animal / Yoriko Otomo and Ed Mussawir -- 19. The life and law of corals: breathing meditations / Irus Braverman -- 20. All that is air melts into city: minoritarian apparatuses for a more-than-human world / Mirko Nikolic -- 21. Listening to the world: sounding out the surroundings of environmental law with michel serres / Danilo Mandic -- 22. F#cking research ethics through radical method: autoethnography and the field of environmental law / Victoria Brooks -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: právo životního prostředí; životní prostředí; environmental law; environment; e-knihy online; e-books online